The Lion, the witch and the wardrobe - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline; HarperCollins Children's Books (London : HarperCollins Children's Books, 1998)
Four English schoolchildren find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch who has cursed the land with eternal winter.
Keywords: Narnia (Imaginary place) -- Fiction; Fantastic fiction